Factors that influence children's gambling attitudes and consumption intentions: lessons for gambling harm prevention research, policies and advocacy strategies. Issue 1 (December 2017) - Pitt, Hannah; Thomas, Samantha; Bestman, Amy; Daube, Mike; Derevensky, Jeffrey
Abstract Background Harmful gambling is a public health issue that affects not only adults but also children. With the development of a range of new gambling products, and the marketing for these products, children are potentially exposed to gambling more than ever before. While there have been many calls to develop strategies which protect children from harmful gambling products, very little is known about the factors that may influence children's attitudes towards these products. This study aimed to explore children's gambling attitudes and consumption intentions and the range of consumer socialisation factors that may influence these attitudes and behaviours. Methods Children aged 8 to 16 years old (n = 48) were interviewed in Melbourne, Australia. A semi-structured interview format included activities with children and open-ended questions. We explored children's perceptions of the popularity of different gambling products, their current engagement with gambling, and their future gambling consumption intentions. We used thematic analysis to explore children's narratives with a focus on the range of socialising factors that may shape children's gambling attitudes and perceptions. Results Three key themes emerged from the data. First, children's perceptions of the popularity of different products were shaped by what they had seen or heard about these products, whether through family activities, the media (and in particular marketing) of gambling products, and/or the alignment of gambling products with sport. Second, children's gambling behaviours were influenced by family members and culturally valued events. Third, many children indicated consumption intentions towards sports betting. This was due to four key factors: (1) the alignment of gambling with culturally valued activities; (2) their perceived knowledge about sport; (3) the marketing and advertising of gambling products (and in particular sports betting); and (4) the influence of friends and family. Conclusions This study indicates that there is a range of socialisation factors, particularly family and the media (predominantly via marketing), which may be positively shaping children's gambling attitudes, behaviours and consumption intentions. There is a need for governments to develop effective policies and regulations to reduce children's exposure to gambling products and ensure they are protected from the harms associated with gambling.